FINANCIAL ANALYSIS OF MANAGEMENT OF THE FINANCIAL STATE OF THE COMPANY AND HIDDEN POINTS OF SHORTCOMINGS OF SUCH ANALYSIS - Коpchykova Inna; Kytaychuk, Tetyana; Krupeinytska, Iryna (European Science, 2023)
The study was conducted to assess the effectiveness of modern methods of financial analysis for decision-making in the field of managing the financial condition of small businesses, in particular for the future. When formulating the objectives and analys